Application of green marketing mix of beauty products on sales through purchase decisions as intervening variable - Satrio, Danang; Yunitarini, Siti; Rizqiani, Nila (Asian Management and Business Review, 2021)
Public awareness in Indonesia in responding to global warming has increased significantly. Increased public awareness plays an important role in providing challenges and opportunities for companies that provide goods or services to create products that are in accordance with their wishes. The challenge is to guarantee that the goods or services provided are safe for consumers and friendly and do not damage the environment. The concept of green marketing mix refers to the satisfaction of customer needs, wants, and desires in relation to the maintenance and preservation of the environment. Discussions on environmental issues in developed countries have been initiated and developed since the 1990s. Green marketing is a marketing concept used by companies to achieve the main goal of making a profit. Green marketing in the process is an act of integrating broad activities, which include product modifications, changes to the production process, changes to packaging, to changes to advertising. Based on this phenomenon, this study aims to find out how much influence the application of the green marketing mix has on sales.